Autonomous public bodies in Mexico and their relevance in the protection of human rights - Rodríguez Canales, José Ángel (Revista Internacional & Comparada de Derechos Humanos, 2025)
The purpose of this chapter is to analyze the figure of autonomous constitutional bodies, starting with the exposition of what they’re known for in a general way and then focusing on the discussion of three specific bodies. Along with describing the functions that they have, it’s considered important to discuss some criticisms that have been made regarding the work of these institutions and to conduct a critical analysis in order to determine whether, according to this author, such appreciations are justified. Also, this document aims to illustrate the ways in which the autonomous bodies contribute to the defense of human rights, maintaining their independence in relation to other entities as a priority.